ANALYSIS OF DIGITAL COMMUNICATIONS OF THE SOUTH TAPANULI REGIONAL GOVERNMENT IN DISTRIBUTING FLOOD DISASTER INFORMATION IN 2025 - Farida Berliana; Hotmatua Paralihan (Journal Analytica Islamica, 2026)
This study aims to analyze the digital communication of the South Tapanuli Regional Government in distributing information about the 2025 flood disaster via Instagram. The method used was a qualitative approach with content analysis techniques on published posts. The results show that the government's digital communication is structured with early warning content, disaster information, assistance, and recovery to increase public awareness and trust. Educational content is most effective, but communication is still one-way. Overall, it is effective, but interactivity and two-way communication are needed to improve public preparedness.